Analysis of Student Reading Interest in the Implementation of Literacy Culture at SD Negeri 1 Gondanglor - Desta Nur Rahmawati; Erna Eka Widiyawati; Zuhrotun Nisak; Syamsul Syamsul (AJER: Advanced Journal of Education and Religion, 2024)
Students interest in reading is currently declining and many are caused by several factors. The problem of education in Indonesia is still focused on the low level of student literacy. This is caused by a lack of interest in reading in students, which is largely influenced by technological advances and the lack of the role of parents and teachers in providing motivation. In fact, by doing reading activities, a person can get a lot of new things, can provide encouragement in finding new information and can broaden his knowledge. The aims of this study were: (1) to find out students' reading interest in SD Negeri 1 Gondanglor (2) to find out the application of literacy culture in SD Negeri 1 Gondanglor (3) to find out students' reading interest with the application of literacy culture in SD Negeri 1 Gondanglor. In research using qualitative research. From the results of research at SD Negeri 1 Gondanglor it can be seen that students' interest in reading at SD Negeri 1 Gondanglor falls into the "moderate" category. Where there are 3 students in the high category with a percentage of 27.3% while 6 students fall into the medium category with a percentage of 54.5% and a percentage of 18.2% is owned by 2 students in the low category. Students' interest in reading at this school is influenced by several factors, namely internal factors and external factors. Internal factors come from within the students themselves while external factors come from teachers and parents.